ANALYSIS OF THE IMPLEMENTATION INDUSTRIAL WORK PRACTICES IN PGRI 2 VOCATIONAL SCHOOLS, SUMEDANG - Bambang Eko Saputro (Sean Institute, 2022)
The purpose of this study is (1). Describing the characteristics of industrial planning work practices in SMK PGRI 2 Sumedang, (2). Describing the characteristics of the implementation of the industrial working practices in SMK PGRI 2 Sumedang, (3). Describing the characteristics of the industrial working practices votes in SMK PGRI 2 Sumedang. The research is a qualitative research with descriptive design. Sources in the research is the principal, vice-principal, the chairman of the working group prakerin, head of program membership, earning of teachers and industry leaders. Methods of data collection are observation, interview, and documentation. Analysis of data using an interactive model. The results of the study are (1) .Perencanaan industry work practices include: mapping industry, prakerin program, prakerin time, debriefing prakerin, and the establishment of a tutor, (2) .Pelaksanaan industry work practices include organizing, prakerin student submissions to the industry, monitoring students prakerin and withdrawal prakerin students to school. (3). Assessment practices industry work there are two stages, namely assessments by tutors industry and counselors School with a parameter value of the industry (IN) is weighted 60%, the value of the journal prakerin (JP) is weighted 10%, the value of the oral exam (UL) is weighted 20% , and the value of the report (LP) is weighted 10%. So that the total value of the results prakerin students are: 0.6 (IN) + 0.1 (JP) + 0.2 (LP) +0.1 (LP).